Morphological characterization and agronomic agronomic agronomic performance - ADOUKONOU-SAGBADJA, Hubert (My University, 2015)
Cashew tree is a multi ashew tree is a multi ashew tree is a multi ashew tree is a multi ashew tree is a multi ashew tree is a multiashew tree is a multiashew tree is a multiashew tree is a multiashew tree is a multi ashew tree is a multiashew tree is a multi ashew tree is a multi -purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro purpose fruit species in Benin. The aim of this study was to evaluate the agropurpose fruit species in Benin. The aim of this study was to evaluate the agro-morphologicalmorphological morphological morphologicalmorphologicalmorphologicalmorphological diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this diversity of the cashew varieties for their better management and utilization in crop improvement. For this purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 qualitative qualitativequalitativequalitativequalitativequalitativequalitative qualitativequalitative and 22 and 22 and 22 and 22 and 22 quantitative quantitative quantitativequantitativequantitativequantitativequantitative quantitativequantitative) agro) agro) agro ) agro) agro-mo rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools rphological descriptors developed by Bioversity International. Statistical tools such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to such as Principal Component Analysis (PCA) and Hierarchical Clustering HCA) tools have been used to describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that p describe the genetic variability. PCA results revealed that pdescribe the genetic variability. PCA results revealed that parameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence arameters related to apple, nuts, kernel and inflorescence are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA are the most important parameters that heavily contribute to overall diversity within cashew species. Based on HCA of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, of the quantitative variables, four four four four phenotypic classes were distinguished with phenotypic classes were distinguished with phenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished withphenotypic classes were distinguished with phenotypic classes were distinguished with in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant in the sampled cashew trees. Significant correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple correlations (positive or negative) were detected between variables such as the length and weight of apple on one one one hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence hand and the weight, length width of nut inflorescence on the other hand. This prelimthe other hand. This prelim the other hand. This prelimthe other hand. This prelim the other hand. This prelim the other hand. This prelimthe other hand. This prelimthe other hand. This prelim the other hand. This prelim the other hand. This prelimthe other hand. This prelimthe other hand. This prelimthe other hand. This prelim the other hand. This prelimthe other hand. This prelimthe other hand. This prelim the other hand. This prelimthe other hand. This preliminary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests inary work suggests the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew the existence of an important genetic variability among Beninese cashew accessions accessions accessions accessions accessions accessions accessions accessions accessions that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding that could be used in a breeding program. program. program. Key Keywords:words:words:words:words: AgroAgro -morphology, morphology, morphology, morphology, morphology, morphology, fruit treefruit treefruit tree fruit tree fruit tree, phenotypic diversity henotypic diversity henotypic diversityhenotypic diversityhenotypic diversityhenotypic diversityhenotypic diversityhenotypic diversity henotypic diversityhenotypic diversity henotypic
Keywords: Agro -morphology; fruit tree; phenotypic diversity